2021
DOI: 10.1002/gepi.22375
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the Laplace effect size prior distribution in Bayesian fine‐mapping studies

Abstract: The Gaussian distribution is usually the default causal single-nucleotide polymorphism (SNP) effect size prior in Bayesian population-based finemapping association studies, but a recent study showed that the heavier-tailed Laplace prior distribution provided a better fit to breast cancer top hits identified in genome-wide association studies. We investigate the utility of the Laplace prior as an effect size prior in univariate fine-mapping studies. We consider ranking SNPs using Bayes factors and other summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…We assume that there is no cost in making the correct decision. There are, therefore, two costs to assign: false discovery cost ( C A ) when INSDENS incorrectly identifies a gene as essential when it is actually non-essential and the false non-discovery cost ( C B ) when INSDENS identifies a gene as non-essential when it is actually essential ( Walters et al , 2021 ). Bayesian decision theory states that gene i is declared to be essential if the posterior cost of declaring it to be essential is less than the posterior cost of declaring it be non-essential.…”
Section: Methodsmentioning
confidence: 99%
“…We assume that there is no cost in making the correct decision. There are, therefore, two costs to assign: false discovery cost ( C A ) when INSDENS incorrectly identifies a gene as essential when it is actually non-essential and the false non-discovery cost ( C B ) when INSDENS identifies a gene as non-essential when it is actually essential ( Walters et al , 2021 ). Bayesian decision theory states that gene i is declared to be essential if the posterior cost of declaring it to be essential is less than the posterior cost of declaring it be non-essential.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, harmonizing heterogeneous datasets with different underlying technologies (such as different arrays, whole exome, or genome sequencing) and including low-frequency variants is thought to be fruitful for further discovery of putative causal variants underlying human complex disorders by increasing the statistical power and the coverage of the genome. Another direction is the optimization of the prior distribution of the causal effect sizes [83,84] (not the causal configuration); for example, Walters et al [83] suggested Laplace prior could increase the statistical power compared to the commonly used normal distribution. As optimizing the prior is a non-trivial problem in Bayesian analysis in general, it could be also valuable to discuss the possibility of moving outside of the Bayesian world to practice statistical fine-mapping in a frequentist approach.…”
Section: Further Extension Of Statistical Fine-mapping Methodsmentioning
confidence: 99%
“…We provide the SNP number from 1 to 1733 (rather than 1 to 90) for the top 10 ranked SNPs. This is for ease of comparison with Walters et al (2021). The prior probabilities of the number of causal SNPs used in this analysis are provided in Table 2.…”
Section: Icogs Analysismentioning
confidence: 99%
“…The Gaussian distribution is not the only distribution that has been considered for the effect size prior in univariate analyses. The t distribution (Marchini & Howie, 2010), the normal‐gamma distribution (Alenazi et al, 2019; Boggis et al, 2016) and the Laplace distribution (Hoggart et al, 2008; Walters et al, 2021) have all been considered. Walters et al (2019) assessed the fit of the Gaussian and Laplace priors using Bayesian model selection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation